An Overview of Life Insurance - Lisa Leslie; Martie Gillen (EDIS)
The primary purpose for buying life insurance is to protect the people who depend on you. A life insurance policy can help to ensure your family’s financial needs are met even after your untimely death. Life insurance can also provide a way to leave a cash gift to your spouse, children, grandchildren, or charities. Once you decide to buy a life insurance policy, you will have a few decisions to make. You will need to select among the different types of life insurance, decide on a dollar amount, and name your beneficiaries. In this publication, you will learn about the different types of life insurance and the ways to determine the amount of life insurance you may need. This 4-page fact sheet was written by Lisa Leslie and Martie Gillen and published by the UF Department of Family Youth and Community Sciences, October 2013.